Confirmed cannibalism in wild boar and its possible role in African swine fever transmission - Cukor, Jan; Linda, Rostislav; Václavek, Petr; Mahlerová, Karolina; Šatrán, Petr; Havránek, František (Transboundary and emerging diseases, 2020)
For the monitoring of wild boar interactions with conspecific carcasses, seven wild boar carcasses were placed in different sites in the Czech Republic during winter season. Data were collected by camera traps. In total, 732 visits were recorded of wild boars at the carcass sites. Direct contact with the carcass was detected in 81% of the records. Cannibalism was observed in 9.8% of all recorded visits. The first direct contact was observed on average 30 days after the carcass had been placed in its respective site. Cannibalism was observed on average after 70 days. The effect of sex-age class on direct contact was not proven in our study. The presented findings show that cannibalism in wild boar can play a substantial role in the ASF epidemic. These results highlighted the importance of the removal of infected carcasses from the habitat, which is crucial for African swine fever eradication.
Keywords: African swine fever; Sus scrofa; cannibalism; Ecosystem; Epidemics; Female; Cannibalism; zvířata; Swine; African Swine Fever; kanibalismus; camera-trapping; roční období; ženské pohlaví; virus afrického moru prasat; Male; wild boar behaviour; Seasons; Czech Republic; epidemie; africký mor prasat; Animals; Česká republika; mužské pohlaví; African Swine Fever Virus; prasata; ekosystém